The oral-brain axis: can periodontal pathogens trigger the onset and progression of Alzheimer’s disease? - Li, Ruohan; Wang, Junnan; Xiong, Wei; Luo, Yu; Feng, Huixian; Zhou, Heng; Peng, Youjian; He, Yan; Ye, Qingsong (Frontiers in Microbiology, 2024)
Alzheimer's disease (AD) is the most prevalent form of dementia, characterized by a progressive cognitive decline. Sporadic AD, accounting for more than 95% of cases, may arise due to the influence of environmental factors. It was reported that Periodontitis, a common oral ailment, shares several risk factors with AD, including advanced age, smoking, diabetes, and hypertension, among others. Periodontitis is an inflammatory disease triggered by dysbiosis of oral microorganisms, whereas Alzheimer's disease is characterized by neuroinflammation. Many studies have indicated that chronic inflammation can instigate brain AD-related pathologies, including amyloid-β plaques, Tau protein hyperphosphorylation, neuroinflammation, and neurodegeneration. The potential involvement of periodontal pathogens and/or their virulence factors in the onset and progression of AD by the oral-brain axis has garnered significant attention among researchers with ongoing investigations. This review has updated the periodontal pathogens potentially associated with AD, elucidating their impact on the central nervous system, immune response, and related pathological processes in the brain to provide valuable insights for future research on the oralbrain axis.